Princípio republicano, cargo em comissão e clientelismo político nos municípios do estado do Rio de Janeiro: reflexões sobre a profissionalização da função pública no Brasil - Amorim, Carlos Alberto Novelino de (2008)
The origin of the desire to get a govemment job in Brazil goes back to the development of the first settlements and vilIages during the colonial period. Nepotism and political patronage pervades the country's history. With the republican principIe as a guide line, we sought to verify to what extent are political appointees utilized in the municipalities of the State of Rio de Janeiro as a strategy to maintain and renew patronage practices and nepotismo The use of methods and techniques of documental analysis and of content, in legal provisions produced by the studied municipalities and in Ordinary Audit Reports made by the Audit Court of the State of Rio de Janeiro, not only alIowed us to proceed with qualitative analysis as welI as the use of quantitative techniques and graphic charts of the findings, alIowing an easier reading and understanding for those who have little contact with the material. This complementarity of methods alIowed the inference that the actions taken by public administrators referring to free nomination are against the practice of citizenship, equalitarianism, and respect of public service. The study demonstrated that almost alI the municipalities studied use political appointees in a manner completely inverse to that foreseen in the constitution. In fact, such positions serve to provide entry to public service to those persons who are related to the administrator, not to assist the administrator, but to increase the family income, fulfill campaign promises and even in exchange for votes. They exercise functions that, by their requirements, should be offered in public civil service exams to all society. FinalIy, the study suggests a set of measures, based on criteria grounded on scientific principIes of administration, to value civil servants, to reduce the degree of politicization of public management and heritable appropriation of public posts, to expedite professionalization of public functions and to restrict the free granting of political appointments as well as to enforce sanctions for administrative improbity on those who disrespect such measures. In regard to the importance of preventive measures, directed toward the development of an attitude in the sense of an authentic public service, the tendency toward permissiveness urgent1y needs to be eliminated.